2023
DOI: 10.1051/0004-6361/202244767
|View full text |Cite
|
Sign up to set email alerts
|

Toward a population synthesis of disks and planets

Abstract: Aims. We want to find the distribution of initial conditions that best reproduces disc observations at the population level. Methods. We first ran a parameter study using a 1D model that includes the viscous evolution of a gas disc, dust, and pebbles, coupled with an emission model to compute the millimetre flux observable with ALMA. This was used to train a machine learning surrogate model that can compute the relevant quantity for comparison with observations in seconds. This surrogate model was used to perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 135 publications
1
4
0
Order By: Relevance
“…First, such high mass-loss rates, as we infer, are not universal to photoevaporation simulations with other treatments finding lower values (Komaki et al 2021, A. D. Sellek et al 2024, albeit at X-ray luminosities somewhat below that used in our best-fitting hiLX_TCha_sUV spectrum (which might be expected to drive a higher mass-loss rate). This is in agreement with studies of disk population synthesis and evolution on secular timescales, where many authors have argued that the higher photoevaporation rates cannot be sustained across the whole population (Sellek et al 2020;Somigliana et al 2020;Appelgren et al 2023;Emsenhuber et al 2023) in order to explain the lifetimes of disks and the observation of disks with large amounts of (dust) mass depletion. The most statistical constraint was calculated by Alexander et al (2023), who showed that the observed distribution of accretion rates is incompatible with a simulated population if the photoevaporation rate exceeds ∼10 −9 M ☉ yr −1 .…”
Section: What Sort Of Wind Do Ne and Ar Trace In T Cha?supporting
confidence: 89%
“…First, such high mass-loss rates, as we infer, are not universal to photoevaporation simulations with other treatments finding lower values (Komaki et al 2021, A. D. Sellek et al 2024, albeit at X-ray luminosities somewhat below that used in our best-fitting hiLX_TCha_sUV spectrum (which might be expected to drive a higher mass-loss rate). This is in agreement with studies of disk population synthesis and evolution on secular timescales, where many authors have argued that the higher photoevaporation rates cannot be sustained across the whole population (Sellek et al 2020;Somigliana et al 2020;Appelgren et al 2023;Emsenhuber et al 2023) in order to explain the lifetimes of disks and the observation of disks with large amounts of (dust) mass depletion. The most statistical constraint was calculated by Alexander et al (2023), who showed that the observed distribution of accretion rates is incompatible with a simulated population if the photoevaporation rate exceeds ∼10 −9 M ☉ yr −1 .…”
Section: What Sort Of Wind Do Ne and Ar Trace In T Cha?supporting
confidence: 89%
“…Our code includes an observational effect by considering as dispersed disks with masses lower than 10 −6 M e ; this simulates a dispersal effect even in the viscous scenario, which would otherwise generate disks with infinite lifetime that do not match the observed disk fraction (see Appendix C). This problem is usually solved in the literature by adding other physical effects to the purely viscous model, such as internal photoevaporation (see, e.g., Hollenbach et al 1994;Clarke et al 2001;Owen et al 2011;Picogna et al 2019;Emsenhuber et al 2023). In order to account for the statistical effect of reducing our sample throughout the evolution caused by disk dispersal, we performed 100 simulations for both setups described in Table 1 and then considered not only the median evolution of the interesting quantities but also the interval between the 25th and 75th percentiles (see Section 3).…”
Section: Population Synthesismentioning
confidence: 99%
“…Instead, Tychoniec et al (2018 provide disk masses for their sample of ∼100 protostellar disks spanning a range of stellar types from F to M, with a median mass (dust + gas) of about 0.075 M e , which would be sufficient to undergo instability through the GDGI mechanism discussed in this work. Emsenhuber et al (2023) studied the lifetimes of protoplanetary disks subject to both internal and external photoevaporation, finding that photoevaporation is likely to be so efficient that a nominal protoplanetary disk disappears within about 1 Myr, even for a disk with an initial mass one-tenth that of its host star. Given observational evidence that typical disk lifetimes are a few Myr, Emsenhuber et al (2023) suggest that the observations can be matched by assuming disks to be more massive and more compact than their nominal disks, while noting that making disks more massive risks making them gravitationally unstable, the situation studied in the present models.…”
Section: M-dwarf Disk Massesmentioning
confidence: 99%
“…Emsenhuber et al (2023) studied the lifetimes of protoplanetary disks subject to both internal and external photoevaporation, finding that photoevaporation is likely to be so efficient that a nominal protoplanetary disk disappears within about 1 Myr, even for a disk with an initial mass one-tenth that of its host star. Given observational evidence that typical disk lifetimes are a few Myr, Emsenhuber et al (2023) suggest that the observations can be matched by assuming disks to be more massive and more compact than their nominal disks, while noting that making disks more massive risks making them gravitationally unstable, the situation studied in the present models. Boyden & Eisner (2023) compared the thermochemical models of protoplanetary disks with ALMA observations of 20 disks in the Orion Nebula Cluster (ONC), finding that the disks are massive (gas masses 10 −3 M e ) and compact (radii less than 100 au), implying that external photoevaporation is just getting underway in the ONC.…”
Section: M-dwarf Disk Massesmentioning
confidence: 99%